Treatment of In-Patient Pulmonary Tuberculosis - Rasmin Rasjid (Indonesian Pediatric Society, 1975)
The progress of a tuberculous lesion was discussed. A treatment regimen of pulmonary tuberculosis in the wards mas layed out, especially for the